2018
DOI: 10.1097/md.0000000000012973
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model of lymphovascular invasion based on clinicopathological factors in Chinese patients with invasive breast cancer

Abstract: The aim of this study was to evaluate the correlation between lymphovascular invasion (LVI) and tumor size, histological grade, and the expression statuses of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor-2 (HER-2), Ki67, epidermal growth factor receptor (EGFR), vascular endothelial growth factor (VEGF), E-cadherin, and P53 in invasive breast cancer, then establish a prediction model of LVI based on the associated clinicopathological factors.A total of 392 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 14 publications
3
21
0
3
Order By: Relevance
“…Additionally, calcification was also an independent predictor of LVI, which was similar to the result obtained in the work of Gajdos et al In addition, patients younger than 45 years and suspicious AUS findings had independent value for predicting ALNM and LVI. Similar results have indicated that the positivity of LVI and ALNM drops in younger (<50 years) patients . Since the menstrual status is age related, both a hormonal effect and time‐dependent exposure might be reasonable explanations .…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, calcification was also an independent predictor of LVI, which was similar to the result obtained in the work of Gajdos et al In addition, patients younger than 45 years and suspicious AUS findings had independent value for predicting ALNM and LVI. Similar results have indicated that the positivity of LVI and ALNM drops in younger (<50 years) patients . Since the menstrual status is age related, both a hormonal effect and time‐dependent exposure might be reasonable explanations .…”
Section: Discussionsupporting
confidence: 77%
“…The prognosis of breast cancer is determined by certain clinicopathological factors, including the presence or absence of lymph node metastasis, tumor size, histological grade, estrogen receptor (ER) status, progesterone receptor (PR) status, human epidermal growth factor receptor-2 (HER-2) status, Ki-67 expression, and the presence or absence of lymphovascular invasion (LVI) [ 1 ]. LVI is the main route of lymph node metastasis and is a known independent predictor of lymph node metastasis, disease-free survival (DFS) and overall survival (OS) in breast cancer [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that LVI is a feature related to poor prognosis and that it promotes local recurrence and distant metastasis of tumours [20]. Several recent studies have recognized LVI as an independent predictor of NSLN metastasis in patients with 1-2 positive SLNs [21,22].…”
Section: Discussionmentioning
confidence: 99%